An Exercise Intervention During Chemotherapy for Women With Recurrent Ovarian Cancer: A Feasibility Study. Issue 6 (1st July 2015) - Mizrahi, David; Broderick, Carolyn; Friedlander, Michael; Ryan, Mary; Harrison, Michelle; Pumpa, Kate; Naumann, Fiona
Abstract : Objective: The aim of this study was to determine the feasibility of a combined supervised and home-based exercise intervention during chemotherapy for women with recurrent ovarian cancer. Secondary aims were to determine the impact of physical activity on physical and psychological outcomes and on chemotherapy completion rates. Methods: Women with recurrent ovarian cancer were recruited from 3 oncology outpatient clinics in Sydney and Canberra, Australia. All participants received an individualized exercise program that consisted of 90 minutes or more of low to moderate aerobic, resistance, core stability, and balance exercise per week, for 12 weeks. Feasibility was determined by recruitment rate, retention rate, intervention adherence, and adverse events. Aerobic capacity, muscular strength, fatigue, sleep quality, quality of life, depression, and chemotherapy completion rates were assessed at weeks 0, 12, and 24. Results: Thirty participants were recruited (recruitment rate, 63%), with a retention rate of 70%. Participants averaged 196 ± 138 min · wk of low to moderate physical activity throughout the intervention, with adherence to the program at 81%. There were no adverse events resulting from the exercise intervention. Participants who completed the study displayed significant improvements in quality of life ( P = 0.017), fatigue ( P = 0.004), mental health ( P = 0.007), muscular strength ( P = 0.001), and balance ( P = 0.003) after the intervention. Participants completing the intervention had a higher relative dose intensity than noncompleters ( P = 0.03). Conclusions: A program consisting of low to moderate exercise of 90 min · wk was achieved by two-thirds of women with recurrent ovarian cancer in this study, with no adverse events reported. Randomized control studies are required to confirm the benefits of exercise reported in this study.